2015
DOI: 10.18052/www.scipress.com/ilns.46.46
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pruning Intensities on the Performance of Fruit Plants under Mid-Hill Condition of Eastern Himalayas: Case Study on Guava

Abstract: ABSTRACT. Current study was undertaken to highlight the effect of pruning on improving vigor of old orchards and increasing performance in terms of fruit yield and quality under water and nutrient stressed condition of mid hills of Eastern Himalaya. Guava was taken for the case study and all the physical and chemical properties of the fruits and other attributes of plant were evaluated using standard methods under three pruning intensities (light, moderate and severe) and no pruning. The emergence of bud was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 8 publications
7
9
0
Order By: Relevance
“…The minimum Acidity (%) was recorded in T4 (30 cm pruning) (0.20%). Similar results have also been reported by Bhagawati et al [25].…”
Section: Resultssupporting
confidence: 92%
“…The minimum Acidity (%) was recorded in T4 (30 cm pruning) (0.20%). Similar results have also been reported by Bhagawati et al [25].…”
Section: Resultssupporting
confidence: 92%
“…The growth parameters were significantly influenced by different treatments. Plants retained with 3 shoots per branch had resulted in maximum plant height (3.16 m), plant girth (12.01 cm), length of the shoot (132.48 cm), girth of the shoot (3.09 cm) this may be attributed to relatively less numbers of shoots and availability of more nutrients per shoots under identical condition which is also reported by Bhagawati et al, (2015) in guava. In the present study lateral buds are stimulated to grow (due to better dry matter partitioning) after pruning due to higher activity of GA-like substances which can be related to the findings by Lian et al, (2019) in guava.…”
Section: Resultssupporting
confidence: 68%
“…Manipulation of tree growth using canopy management practices to control tree growth patterns, tree shape for high fruit production of desired size and quality (Singh, 2001). The thinning of shoots per branch is also one of the canopy management practices in the rejuvenation of old orchards (Bhagawati et al, 2015). Nutrients can be made available to the plants by the basal as well as foliar application.…”
Section: Issn: 2319-7706 Volume 8 Number 10 (2019)mentioning
confidence: 99%
“…This finding indicates that pruning improves the proportions of vegetative and generative plant parts (Ambroszczyk et al, 2007). Many researchers have found that pruning can improve fruit yield and quality by enabling greater access to light, water and nutrients (Reynolds, 1989;Seifi et al, 2011;Bhagawati et al, 2015). However, we also observed a non-linear relationship between pruning intensity and fruit yield.…”
Section: Discussionsupporting
confidence: 51%